FACTORS CONTRIBUTING TO LATE ANTENATAL CARE BOOKING AMONG PREGNANT WOMEN IN BUDUDA HOSPITAL IN BUDUDA DISTRICT. - Okwany, Jimmy; Kimono , Annamary (Student's Journal of Health Research Africa, 2023)
Purpose of the study: ANC booking is the first visit made by a pregnant woman. Despite of government’s commitment in provision of free ANC services most of the pregnant women have continued to delay booking and they have ended up with complications related to delay in diagnosis and management of pregnancy related conditions. Objectives: The study is aimed at determining factors contributing to late ANC booking among pregnant women in Bududa hospital with the specific objectives being; to find out individual related factors, to establish health related factors and to assess community related factors contributing to late ANC booking among pregnant women in Bududa Hospital. Study methods/design: A descriptive cross-sectional hospital based survey with both quantitative and qualitative approach as the research design conducted at ANC clinic in Bududa hospital in Bududa District in February. Altogether 95 respondents were taken and the respondents were pregnant women who had attended Antenatal care services in the hospital. Study findings: The proportion of pregnant women who booked late for ANC in Bududa hospital was found to be 89%s. It was high and significant in age groups above 20 years i.e. between 20 to 30 years; 15 out of 25 pregnant mothers were late for ANC while those between 31-40years; 30 out of 35 came late, and almost all pregnant mothers above 40 years presented late for ANC (24 out of 25). Married pregnant women were 79% and pregnant women who had support were 78%. Conclusions: Pregnant women came late for ANC booking because they lacked support, distance, poverty, waiting for abdomen to enlarge, prohibited by husband, poor communication by health workers, bad weather, being rescheduled at the time of booking among others.